Strategi Pengembangan Bisnis UMKM Mie Ayam Pak Sorodi: Optimalisasi QRIS, Pemanfaatan Media Sosial, dan Desain Visual untuk Pertumbuhan Usaha - Sharon Miscal Pricilla; Felisita Sekar Larasati; Juwita Amanda; Resya Adia Pramesti; Jericho Nathanael; Vicky Aditya; Santi Rimadias (Lembaga Pengembangan Kinerja Dosen, 2025)
The culinary industry in Indonesia is one of the fastest-growing sectors of the creative economy, contributing approximately 41% to the total GDP of the creative economy in 2020. However, product marketing challenges remain a significant obstacle for Micro, Small, and Medium Enterprises (MSMEs) in this sector. Issues such as limited marketing skills, intense competition, and restricted access to digital technology hinder MSMEs' competitiveness. Mie Ayam Pak Sorodi, as one of the MSMEs, faces challenges in digital marketing, including the absence of digital payment systems and social media platforms. This community service aims to assist the MSME in adopting digital transformation by creating social media profiles, adding business locations to Google Maps, and implementing QRIS payment systems. The methods include direct mentoring and technical training for business owners. The results indicate an improvement in market reach, customer engagement, and operational efficiency. This digital transformation is expected to enhance competitiveness and business sustainability in an increasingly competitive market (Ftindustri, n.d.).